2011
DOI: 10.1039/c0gc00667j
|View full text |Cite
|
Sign up to set email alerts
|

HPLC-EAT (Environmental Assessment Tool): A tool for profiling safety, health and environmental impacts of liquid chromatography methods

Abstract: A simple and efficient approach for profiling the greenness of high performance liquid chromatography (HPLC) methods is presented. This environmental assessment tool (EAT) takes into consideration the environmental, health and safety issues for all solvents involved in the chromatographic method, and calculates a total score that can be used for comparison of the greenness of different methods. A software, HPLC-EAT, has been designed to facilitate the calculation and can be downloaded free of charge at http://… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(87 citation statements)
references
References 28 publications
0
85
0
2
Order By: Relevance
“…The substitution of acetonitrile by methanol had two main reasons. The first intended to minimize mobile phase eluotropic force to get a more slightly gradient, and the second intended to use a more health and environment friendly solvent, since acetonitrile is more toxic than methanol [36]. Although the time of analysis was increased in 10 minutes, the flow rate could be reduced, allowing the reduction of solvent consume.…”
Section: Discussionmentioning
confidence: 99%
“…The substitution of acetonitrile by methanol had two main reasons. The first intended to minimize mobile phase eluotropic force to get a more slightly gradient, and the second intended to use a more health and environment friendly solvent, since acetonitrile is more toxic than methanol [36]. Although the time of analysis was increased in 10 minutes, the flow rate could be reduced, allowing the reduction of solvent consume.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few exceptions however. In Gaber et al [56], an environmental assessment tool (EAT) was developed for HPLC methods using EHS data. The new software tool is called HPLC-EAT.…”
Section: Green Metricsmentioning
confidence: 99%
“…In fact, Gaber et al (Gaber et al, 2011) suggested that the greenness should be incorporated during analytical method development, along with the conventional standards of accuracy, robustness, selectivity, and reproducibility. In the present section of the chapter we will show some examples of quantification of the green profile of some analytical techniques used in foodomics.…”
Section: Comparative Lca Study Of Green Analytical Techniques: Case Smentioning
confidence: 99%